Metal Dust Exposure and Respiratory Health of Male Steel Work¬ers in Terengganu, Malaysia - Nurul Ainun HAMZAH; Shamsul Bahri MOHD TAMRIN; Noor Hassim ISMAIL (Tehran University of Medical Sciences, 2015)
Background: This cross sectional study was carried out to determine the relationship between metal dust exposure and respiratory health in male steel workers in Terengganu, Malaysia. Methods: Subjects were interviewed using a structured questionnaire from British Medical Research Council (BMRC) Questionnaire regarding respiratory symptoms and were examined their lung function using spirometer. Results: The mean trace metal dusts concentration TWA8 for cobalt and chromium in most of work unit exceeded occupational exposure prescribed values. Prevalence of chest tightness, chronic phlegm, and shortness of breath was 28.0%, 26.8%, 24.1%, and 20.2% respectively. Age and smoking were among the factors associated with respiratory symptoms (OR: 0.92 - 1.78). Smoking and cumulative respirable metal dust were negatively associated with FEV1. Conclusion: The mean metal dust for cobalt and chromium were 1 to 2 times higher than permissible exposure limit (PEL). This study found that respirable cumulative metal dust exposure is one of the contributing factors to lung function values among steel workers.   Keywords: Respiratory symptoms, Lung function, Metal dust, Questionnaire